DIGITALIZATION AND ESG SYNERGIES. TRANSFORMING REGIONAL DEVELOPMENT THROUGH CORPORATE ACTIONS - SPULBAR LUCIAN FLORIN; MITRACHE DANIEL MARIUS; MITRACHE LAVINIA ADELINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
As global corporations increasingly prioritize Environmental, Social, and Governance (ESG) criteria, the role of digitalization in achieving sustainable regional development has come into sharp focus. This article examines how corporations, through digital transformation and ESG initiatives, are reshaping the socio-economic landscapes of the regions they operate in, aiming to create a more sustainable, inclusive, and resilient future. The synergy between digitalization and ESG practices not only aligns with corporate growth and profitability but also with regional goals for economic advancement, environmental sustainability, and social equity. Digital technologies facilitate more effective compliance with ESG criteria, allowing corporations to monitor and manage their environmental footprints, ethical practices, and community engagement efforts in real-time. As a result, the integration of digitalization with ESG principles is transforming the way corporations interact with and contribute to regional development. This article also explores the direct impacts of corporate digitalization on local employment, education, and infrastructure. By investing in digital skills training, companies enhance workforce capabilities and foster economic resilience within local communities. Furthermore, corporate commitment to ESG drives sustainable practices in resource-dependent regions, supporting efforts in areas like renewable energy, waste reduction, and biodiversity preservation. However, challenges remain in ensuring that the benefits of digital transformation and ESG adoption are widely distributed. This article delves into potential risks, such as data privacy issues, digital divides, and the need for stronger regulatory frameworks to guide corporate behavior. It emphasizes that meaningful corporate contributions to regional development require collaboration with governments, NGOs, and local stakeholders.